(untitled) (Beacon: International Journal of Education and Social Studies, 2025)
Urbanization has become one of the primary drivers of social and cultural transformation in many regions, including Riau Province, Indonesia. Rapid urban development contributes positively to economic growth and modernization but also poses significant challenges to the preservation of traditional culture and local wisdom. This study aims to examine the role of local wisdom in addressing urbanization challenges and to evaluate the social changes affecting traditional culture in Riau. A qualitative research approach was employed using purposive sampling techniques. Data were collected through in-depth interviews, focus group discussions (FGDs), and participant observations involving traditional leaders, cultural practitioners, academics, and community members with extensive knowledge of local cultural dynamics. The findings reveal that urbanization has altered cultural spaces, social interaction patterns, and traditional practices within local communities. Nevertheless, local wisdom has demonstrated remarkable resilience through various adaptive strategies, including cultural festivals, revitalization of traditional practices, digital documentation of cultural heritage, and the integration of cultural values into urban development initiatives. Furthermore, local wisdom continues to play a significant role in maintaining social cohesion, strengthening cultural identity, and supporting sustainable development. The study concludes that urbanization does not necessarily result in the disappearance of traditional culture; instead, it can provide opportunities for the development of innovative and adaptive forms of cultural preservation that remain relevant in contemporary society.